Os pescadores da Praia do Paquetá (Canoas/RS): entre cotidiano e memória - Ritter, Paulo Roberto (2016)
The present study had as its theme, fisherfolk inhabiting the Paquetá Beach, a small village that is part of the neighborhood Mato Grande, in the city of Canoas, RS. The work is part of the line of research "Memory, Culture and Identity", the Graduate Program in Social Memory and Cultural Heritage - the Unilasalle Canoas. The objective we sought to examine the way of life of Paqueta Beach fishermen, from the understanding of their daily lives. From the dissertation were prepared two products in order to meet the requirements of a professional master, namely: a visual essay on the daily lives of fishermen and traveling exhibition that will visit schools of public and private networks of Canoas Municipality (RS). Theoretically, the study was supported in conceptions about the daily life of Michel Maffesoli and methodologically worked out with Oral History. As a result we have that family ties that comprise the fishermen in their daily lives, strengthen togetherness, lifestyle and make art in their common desire and almost playful to continue to be fishermen and exercise this office, despite all the economic constraints or the nature in a highly urbanized and industrial town.